2020
DOI: 10.1108/rbf-06-2020-0123
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the effect of COVID-19 outbreak on the development of branchless banking in Iran: case study of Resalat Qard–al-Hasan Bank

Abstract: PurposeCOVID-19 has become a global challenge with a significant rate of prevalence, and it has exerted devastating consequences in epidemic, economic and social terms. Therefore, a number of studies have already been, or are now being, conducted on the detrimental effects of the virus. In this respect, a question may arise: Is there any possibility to turn the threat of the virus outbreak into an opportunity in some sectors such as the banking industry? In this research, the effects of COVID-19 outbreak as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Even in times of crisis, unlike conventional banks, Islamic equity funds provide hedging benefits to various market stakeholders, such as during the pandemic. Times of crisis can be used as an opportunity by Islamic banks to invest in policy formulation for reducing inequalities [25]. Islamic banks are offering a practical solution to it, hence, it can be idealized by other businesses to reduce inequalities and promote fair principles for profit-sharing during the COVID-19 pandemic.…”
Section: The Covid-19 Response: Based On Alpha and Betamentioning
confidence: 99%
See 2 more Smart Citations
“…Even in times of crisis, unlike conventional banks, Islamic equity funds provide hedging benefits to various market stakeholders, such as during the pandemic. Times of crisis can be used as an opportunity by Islamic banks to invest in policy formulation for reducing inequalities [25]. Islamic banks are offering a practical solution to it, hence, it can be idealized by other businesses to reduce inequalities and promote fair principles for profit-sharing during the COVID-19 pandemic.…”
Section: The Covid-19 Response: Based On Alpha and Betamentioning
confidence: 99%
“…The pandemic has allowed an opportunity for every business sector [25] to transform and introduce green products and services in compliance with the UN SDGs. This is because linking products and services with the UN SDGs offers great security, and it is expected that those products and services will be least affected in future pandemics due to their prudence.…”
Section: The Covid-19 Response: Based On Alpha and Betamentioning
confidence: 99%
See 1 more Smart Citation
“…At that time the JCI trend was indeed bearish. The effects of the Covid-19 pandemic have occurred in almost all world exchanges, so that many stock prices have fallen (He, Sun, Zhang, & Li, 2020;Singh, Dhall, Narang, & Rawat, 2020;Shahabi, Azar, Faezy Razi, &Fallah Shams, 2020 andAnh &Gan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, Ozili, & Arun, (2020) claimed that even card payments and FinTech transitions declined during the pandemic. Shahabi et al, (2020) suggested that the outbreak of COVID19 has played a key role in changing the attitude of people towards branchless banking in Iran. Banks has insulated itself from the impact of Covid19 and witnessed an increase in online banking and digital payments amid the pandemic crisis.…”
Section: Bankingmentioning
confidence: 99%